STRATEGI EFEKTIF DALAM PROGRAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SMA MUHAMMADIYAH 2 BOJA - Suryani; Dr.H.Mukhamad Anieg,Lc,Ma (As-Sulthan Journal of Education, 2025)
The purpose of this study is to describe and analyze the extent to which the Islamic Religious Education (PAI) learning program at SMA Muhammadiyah 2 Boja is effective. In an era of increasingly complex changes, the challenges faced in religious education are not only limited to the delivery of material, but also the success in instilling religious values in students. This study applies a descriptive qualitative method with data collection through observation, interviews, and documentation. The research findings indicate that the success of the PAI program at SMA Muhammadiyah 2 Boja comes from a combination of active learning methods, role models from teachers, and support in the form of extracurricular religious activities. These results highlight the importance of a comprehensive approach in Islamic religious education to produce students with religious character and good morals.